2020
DOI: 10.1088/1757-899x/671/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study with kinematic and kinetic descriptions of the effect of high-heeled shoes in healthy adult females based on gait analysis

Abstract: Many women remain unaware of the negative effect of high-heeled shoes and the damage and significant changes they can cause in the human body. Studying the effect of high heels during walking shows biomechanical changes in the person wearing the shoes based on their influence on ankle joints, foot pressure distribution, and muscle activity, and changes in Ground Reaction Forces. This study examined the effects of high heels and smooth-soled court shoes using gait analysis. Experiments were conducted on five he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…What's more, in modern fashion, extraordinary heel heights exceeding 12cm (5 inch), or even 'heelless heels" [27], are seen. Although there are not enough studies about the effect of such HH of the foot, women have already been advised not to wear HH higher than 5cm (about 2 inch) [28,29]. To a certain extent, the effect of these extraordinary HH would be expected to be similar to the documented effects of HH, which worsen as the heel height increases.…”
Section: Plos Onementioning
confidence: 99%
“…What's more, in modern fashion, extraordinary heel heights exceeding 12cm (5 inch), or even 'heelless heels" [27], are seen. Although there are not enough studies about the effect of such HH of the foot, women have already been advised not to wear HH higher than 5cm (about 2 inch) [28,29]. To a certain extent, the effect of these extraordinary HH would be expected to be similar to the documented effects of HH, which worsen as the heel height increases.…”
Section: Plos Onementioning
confidence: 99%
“…Biomechanical studies have revealed that high heels cause significant changes in the musculoskeletal system's movement (kinetic) and position (kinematic), affecting the entire body from the spine to the toes. These changes increase the risk of MSK disorders, including osteoarthritis, hallux valgus (HV), and general MSK discomfort (12). Epidemiological evidence firmly establishes a connection between high heel use and an increased risk of hallux valgus (HV), musculoskeletal pain, and injuries to the wearer (13).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is made clinically with no need for imaging [ 3 ]. The evaluation of tibial rotation depends on several anatomical landmarks, one of them is the tibial tuberosity [ 2 , 4 ]. In Asians, the upper end of the tibia exhibits more external rotation (i.e., the tibial shaft exhibits more intorsion).…”
Section: Introductionmentioning
confidence: 99%